Correlates of over- or under-estimation of body size among resource-poor urban dwellers in a sub-Saharan African city - Aaron Kobina Christian; Grace Agyemang Frempong (Taylor & Francis Group, 2020)
Background Individual perception of body size has implications for lifestyle behaviours including dietary habits and weight management practices. Aim To examine factors related to respondents' estimation of their body sizes compared to their body mass index (BMI). Subjects and methods This cross-sectional survey comprised a sample of 917 adults in urban poor Accra, Ghana. Silhouette figure ratings were used to assess perceived body size and ideal body size at a community level. Logistic regression analysis was used to determine correlates of respondents overestimating or underestimating their body sizes. Results Approximately, 69% of respondents either underestimated or overestimated their body sizes. About a quarter of respondents perceived being overweight as the preferred ideal body size in their communities. The mean BMI of females and males who underestimated their body sizes were within the overweight category and normal weight category, respectively. Gender, educational level, employment status, the community of residence, and ethnicity were associated with how respondents correctly estimated, over- or under-estimated their body sizes. There was evidence of ethnicity mediating the association between the community of residence and body size estimation. Conclusion Weight management interventions must be mindful of the socio-demographic and cultural proclivities of the targeted populace for optimum impact.